Risk management strategies and therapeutic modalities to tackle COVID-19/SARS-CoV-2 - Syed Muhammad Ali Shah; Tahir Rasheed; Komal Rizwan; Muhammad Bilal; Hafiz M.N. Iqbal; Nasir Rasool; Sebastian Toma; Luigi Geo Marceanu; Elena Bobescu (Elsevier, 2021)
The recent emergence of novel coronavirus disease (COVID-19) triggered by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) has resulted in substantial mortality worldwide. Presently, there is no approved treatment for COVID-19. Consequently, the clinical, scientific, and regulatory authorities have joint efforts to reduce the severe impact of COVID-19. To date, there is minimal arsenal with no definite curative drugs, licensed-vaccines, or therapeutic conducts to combat the COVID-19 infections. Keeping in view the threats of this pandemic, various global organizations, physicians, researchers, and scientists, are trying to recognize the epidemiological characteristics and pathogenic mechanisms of COVID-19 to discover potential treatment regimens, vaccines, and therapeutic modes for future anticipation. Herein, we summarize a contemporary overview of curative invasions and vaccines for COVID-19 based on the earlier information and considerate of similar earlier RNA coronaviruses. The information reviewed here establishes a paramount intellectual basis to promote ongoing research to develop vaccines and curative agents. Thus, this review suggests the furthermost accessible frontiers in the vaccine development to tackle or combat the COVID-19/SARS-CoV-2.